Relationship between osteoporosis, multiple fractures, and egg intake in healthy elderly - Roberta Pujia; Yvelise Ferro; Samantha Maurotti; Rosario Mare; Franco Arturi; Tiziana Montalcini; Arturo Pujia; Elisa Mazza (Wolters Kluwer Medknow Publications, 2021)
Context: The role of dietary patterns in the prevention of osteoporosis has been investigated in many studies, but few have examined the association between consumption of specific food and whole-body (WB) bone mineral density (BMD). Recent evidence suggests that whole eggs contain bioactive compounds that could have beneficial effects on BMD. BMD is also expressed as the T-score, which is used for the clinical diagnosis of osteoporosis and to evaluate the effectiveness of drugs. Aims: We conducted a study to assess the association between eggs consumption and bone density in a population of the elderly. Settings and Design: This cross-sectional study included 176 individuals of both genders and aged ≥65 years. Subjects and Methods: Egg intake was ascertained by a combination of dietary intake assessment, and a dual X-ray absorptiometry scan was performed to measure WB T-score. Results: In our study, among all the food groups and nondietary factors evaluated, we find a positive association between the WB T-score and egg consumption (B = 0.02; P = 0.02), gender (B = 0.85; P < 0.001), and body mass index (B = 0.04; P = 0.03). Multiple fractures were associated with the daily intake of eggs (B = ‒0.26; P = 0.02) and high-density lipoprotein-cholesterol (B = 0.09; P = 0.03). Conclusions: This study provides novel evidence of a positive link between whole egg consumption and bone health. If results observed in this study will be confirmed through future randomized controlled trials, whole eggs may represent a viable strategy to prevent osteoporosis and reduce the risk of fractures in the elderly.